2023
DOI: 10.3390/nu15030621
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Diet in Tinnitus Onset: A Hospital-Based Case-Control Study from Italy

Abstract: Knowledge on the role of diet in tinnitus onset is mostly based on few cross-sectional studies. In 2016–2019 we conducted a hospital-based case-control study in northern Italy on 185 incident idiopathic tinnitus cases and 198 controls, providing data on dietary habits through a 37-item food-frequency questionnaire. Odds ratios (OR) for tinnitus risk were derived through unconditional multiple logistic regression models. Moderate-to-high vs. low intake of caffeine (OR, 0.49; 95% confidence interval (CI), 0.24–0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A UK study involving over 34,000 adults revealed that elevated calcium, iron, and fat intakes were linked to heightened tinnitus odds. In contrast, increased intakes of vitamin B12 and adherence to a dietary pattern rich in meat intake were associated with reduced odds of tinnitus [ 40 ]. This study underscored the potential influence of nutrients on the onset of tinnitus.…”
Section: Reviewmentioning
confidence: 99%
“…A UK study involving over 34,000 adults revealed that elevated calcium, iron, and fat intakes were linked to heightened tinnitus odds. In contrast, increased intakes of vitamin B12 and adherence to a dietary pattern rich in meat intake were associated with reduced odds of tinnitus [ 40 ]. This study underscored the potential influence of nutrients on the onset of tinnitus.…”
Section: Reviewmentioning
confidence: 99%
“…The first studies conducted in humans suggest that dietary factors have an important role in the onset and severity of tinnitus. Jarach and colleagus [30] provide the first evidence for an inverse association between tinnitus onset and a diet characterized by protein-rich food and caffeine and highlight the importance of food variety: the variety of food decreased the risk of tinnitus (OR 0.47; 95% CI, 0.24-0.90). Marcrum and coauthors [31] show that the intake of caffeine, alcohol, and salt has a mild effect on tinnitus severity, but only in a small proportion of patients.…”
Section: Introductionmentioning
confidence: 98%